CVD as the Result of Cancer Treatment - Vinall, Maria (MD Conference Express, 2013)
Patients undergoing treatment for cancer are at higher risk for cardiovascular disease (CVD), in part because of common risk factors. This article discusses how reduced functional status following cancer treatment can lead to shortened survival in cancer and CVD.